Pengaruh Penggunaan Metode Sima’i Terhadap Kualitas Hafalan Al-Qur’an Santri Pondok Pesatren Al-Qomariyah - Fitriani, Irma; Masitah, Widya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The Qur'an is a divine treatise delivered by Allah SWT from the time of the Prophet Adam until the end of the Prophet's time even until the end of time. The Qur'an teaches humans about daily life so that it helps individuals to be better in behavior and action, helps improve the quality of life in accordance with Islamic law and diridoi Allah, and brings Muslims from the dark ages into a bright age. The Qur'an is the unique Word of God, so we should study it, live it, understand it, and practice its meaning in our daily lives. The first step in creating a generation of Quranic guardians is to learn to read and memorize the Quran. Memorizing the Quran is a very noble act, the dilemma today is that many people consider memorizing the Quran as a mere formality. Many educational institutions pursue quantitative goals but forget about quality. This research was conducted to find out the state of the tahfidz program that uses the sima'i method and how influential the sima'i method is in influencing the quality of memorization of students undergoing the tahfidz program at Pondok pesatren al-qomariyah. this research uses a correlation method with a quantitative approach. The data collection technique starts from observation and tests in the form of pretests and posttests, then the data will be managed through SPSS with the Paired Samples Test test, which states that the value is smaller than 0.05. It can be concluded that the sima'i method that has been carried out does not provide a relationship and there is also no difference in the quality of memorization of the Qur'an of the students of the al-qomariyah pesatren cottage.